Wealth transfers via equity transactions - Sloan, Richard G.; You, Haifeng (Journal of Financial Economics, 2015)
Previous research indicates that firms issue shares when their stock is overpriced and repurchase shares when their stock is underpriced. Such transactions transfer wealth from transacting stockholders to ongoing stockholders. We quantify the magnitude of these wealth transfers and analyze their implications. Strikingly, we find that for the average firm-year, these wealth transfers approximate 40% of net income. We also find that these wealth transfers can be predicted using a variety of firm characteristics and that future wealth transfers are an important determinant of current stock prices.